2016
DOI: 10.1016/j.jas.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene/early Holocene maritime interaction in Southeastern Indonesia – Timor Leste

Abstract: This study analysed over 1000 obsidian stone artefacts excavated from two adjoining shelters at Tron Bon Lei on Alor Island Indonesia using portable XRF. The study showed an unambiguous separation of three different source locations (Groups 1, 2 and 3). Two sources (Group 2 and 3a, b, c) dominate the assemblage numerically. Group 1 and 2 indicate use of a single volcanic formation with a strong match between Group 1 artefacts and artefacts from sites in Timor Leste. Obsidian occurs in the earliest occupation l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…The development of trade not only between neighbouring islands (e.g. Reepmeyer et al , ) but also more extensively throughout the archipelago is rendered more likely considering the extent of relative intervisibility throughout the region. Intermittent occupation records, such as those of Leang Sarru in the Talauds (Ono et al , ), might be explained by an archipelago with such extensive inter‐island connections that a remote colony could easily move back to a larger island if conditions on the smaller island became less favourable.…”
Section: Discussionmentioning
confidence: 99%
“…The development of trade not only between neighbouring islands (e.g. Reepmeyer et al , ) but also more extensively throughout the archipelago is rendered more likely considering the extent of relative intervisibility throughout the region. Intermittent occupation records, such as those of Leang Sarru in the Talauds (Ono et al , ), might be explained by an archipelago with such extensive inter‐island connections that a remote colony could easily move back to a larger island if conditions on the smaller island became less favourable.…”
Section: Discussionmentioning
confidence: 99%
“…The high density of fish bones recorded by Samper Carro et al (2016), in combination with the lithic artefacts found throughout the archaeological sequence (Reepmeyer et al 2016) points to periods of human site use with various subsistence activities. Avian predators are unlikely to inhabit the rock shelter while humans are present.…”
Section: Discussionmentioning
confidence: 95%
“…The maintenance of the relationship between Kisar and Timor can be found in the rock art, oral history, language, and place names that are used together (O'Connor and Ono 2013;O'Connor et al 2018). Considering their developed seafaring culture (O'Connor, Ono, and Clarkson 2011) and indisputable evidence of the maritime transportation of obsidian between islands in the Lesser Sunda found by Reepmeyer et al (2016Reepmeyer et al ( , 2019, early and continuous cultural linkages between the two islands have been demonstrated. Such an abandonment scenario would account for the hiatus in the record, with reoccupation only occurring after climate stabilisation in the Mid-to Late Holocene and supported by the later arrival of Neolithic cultures.…”
Section: Discussionmentioning
confidence: 99%